Exploring the association of legalisation status of cannabis with problematic cannabis use and impulsivity in the USA - Louise Destrée; Danielle Amiet; Adrian Carter; Rico Lee; Valentina Lorenzetti; Rebecca Segrave; George Youssef; Nadia Solowij; Murat Yücel (BioExcel Publishing Ltd, 2018)
Background: There has been an increased trend towards the legalisation of medicinal and recreational cannabis use worldwide. This has been controversial as the long-term effects of frequent cannabis use on the brain are still poorly understood. Methods: In this study, we investigated whether the legal status of cannabis in the United States of America (USA) is associated with problematic cannabis use and impulsivity in 329 frequent cannabis users. The data were collected in 2015 and were analysed in 2017. Ethical approval for this study was obtained from Monash University in 2015. Results: The results indicated that participants' problematic cannabis use and impulsivity was not different whether they resided in states where cannabis is legal for medical and/or recreational use or prohibited. Limitations: The present study is a cross-sectional design, making it difficult to infer causality and establish whether cannabis use is a cause, consequence, or correlate of altered impulsivity. Conclusion: Our study supports the notion that frequent cannabis use is associated with impulsive behaviours, whilst, conversely, we did not find an association between US state legalisation and problematic cannabis use or impulsivity.